1990
DOI: 10.1002/mus.880130403
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and surface EMG diagnosis of pediatric muscle disease

Abstract: The ratio of acoustic myography (AMG) amplitude to surface electromyography (EMG) amplitude is proposed as a measure of mechanical output compared with electrical activity of the contractile system. AMG to EMG ratios were measured from 16 children with muscle disease diagnosed by clinical criteria, EMG, and/or muscle biopsy. These were compared with the ratios from 11 normal volunteers spanning the same age range (7-16 years). AMG to EMG ratios were significantly (P less than 0.01) different for the two popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 9 publications
1
80
1
Order By: Relevance
“…In general, EEA was determined to improve (ie, greater force production was accompanied by decreases in EMG amplitude) with training-induced increases in strength and deteriorated with a fatiguing task. 15,16 Barry et al 7 suggested the dissociation between the electric and mechanical events of muscle function (ie, electromechanical coupling) might be better captured through examination of changes in the ratio of MMG to EMG amplitudes, which creates an index of ''electromechanical efficiency'' (EME).…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, EEA was determined to improve (ie, greater force production was accompanied by decreases in EMG amplitude) with training-induced increases in strength and deteriorated with a fatiguing task. 15,16 Barry et al 7 suggested the dissociation between the electric and mechanical events of muscle function (ie, electromechanical coupling) might be better captured through examination of changes in the ratio of MMG to EMG amplitudes, which creates an index of ''electromechanical efficiency'' (EME).…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%
“…For example, MMG has been used to noninvasively provide diagnostic information about muscular diseases such as spastic cerebral palsy, 6 pediatric neuromuscular disorders, 7 and muscular dystrophy, 8,9 as well as to determine age-related changes in muscle function 10 and to assess muscle fiber composition. 11 In nonclinical populations, authors 2,[12][13][14] have reported a close relationship between MMG amplitude and torque production during repeated, concentric muscle actions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electromyography (EMG), which measures electrical potentials generated by muscle cells, is one such technology. Driven by the growing societal recognition of the needs of people with physical disabilities, researchers are using EMG to diagnose muscular diseases, assess progress in muscular rehabilitation, and directly control prosthetics [1,8,9,11,18]. In these systems, researchers use detailed knowledge of the human physiology to apply sensors, measure activity in specific muscles, and infer intended or unintended movements from recorded data.…”
Section: Introductionmentioning
confidence: 99%
“…Using the ratio of SEMG electrical amplitude to acoustic amplitude, children with Duchenne, Becker, and myotonic dystrophy had significantly higher ratios than normal control subjects. 8 Similarly, using the ratio of the root mean square SEMG amplitude to the mechanomyogram amplitude, the electromechanical coupling efficiency of some muscles was statistically different in patients with myotonic dystrophy (all with CTG expansion) compared with that of age-matched control subjects. 9 In a brief report, 10 SEMG activity in one patient with myotonia congenita and transient weakness showed a decline in mean root SEMG voltage compared with that of a patient without transient weakness and a single control.…”
mentioning
confidence: 99%